AIR QUALITY AT VENUES OF MIXED SMOKING POLICIES IN KAZAKHSTAN - Sadykova, Jamilya; Baizhaxynova, Ardak; Crape, Byron (Tobacco Induced Diseases, 2020)
Enclosed designated smoking areas (DSAs) and smoking zones are allowed in food-serving venues in Kazakhstan. Air quality in smoke-free foodserving venues, in venues with smoking throughout, in those with DSAs and those with smoking zones, is not fully understood.
Keywords: Type of access: Open Access; designated smoking areas; smoking policy; air quality; Kazakhstan